Spectrum Utilization Efficiency of Elastic Optical Networks Utilizing Coarse Granular Routing (Informatica, 2018)
In this paper, we have investigated an elastic optical network that uses coarse granular routing based on our recently developed coarse granular node architecture. The developed coarse granular optical cross-connect (OXC) architecture that enables routing bandwidth-flexible lightpaths coarse-granularly is based on coarser granular selective spectrum switches. The network takes the advantages of both elastic optical networking and coarse granular routing technologies to cope with the trade-off between the link cost and the node cost in order to build a spectrum-and-cost efficient solution for future Internet backbone networks. We have evaluated the hardware scale requirement and the spectrum utilization efficiency of the network with typical modulation formats under various network and traffic conditions. We also compared the spectrum utilization of our network to that of corresponding traditional WDM network and conventional elastic optical network. Numerical results verified that, similar to conventional elastic optical network, the proposed network offers a substantial spectrum saving comparing to traditional WDM network.